Aggregation algorithm for MPLS multicast flows based on bidirectional shared tree - LI Ling-zhi1; ZHU Yan-qin1; YANG Zhe1 (Tongxin xuebao)
Scalability is the mainly problem that impedes the extensive deployment of multicast in MPLS networks. An aggregation algorithm for multicast flow based on bidirectional shared tree was proposed in order to resolve the problem. The aggregated degrees of multicast flows were computed according to the relation among nodes. The label edge routers were clustered into the sets of leaf nodes on shared trees,and tree manager server computed the topology of bidirectional shared trees. The multicast flows,whose aggregated degrees were greater than the specific threshold,were finally con-verged into the trees. The test result indicates that it can greatly reduce the occupation of MPLS labels. The processes of medium nodes are simplified and the forwarding states of routers are reduced in the algorithm. It will greatly enhance the scalability of MPLS multicast.